IMPLEMENTASI METODE APRIORI DALAM MENENTUKAN BIJI KOPI YANG PALING DIMINATI KONSUMEN PADA ROASTERY WARKOP LANGGANO - Novita Sari , Luky; Sucipto , Hadi (Inovate, 2023)
The Warkop Langgano Roastery is one of them competing in the current food and beverage business. The purpose of this study was to find out the implementation of the Apriori Method in determining the most popular coffee beans at the Warkop Langgano Roastery. This research uses the Web-based Apriori method, and data collection through literature study is carried out by studying literature theories from books, journals, references related to this research to complete the data. The results of this study indicate that the implementation of the a priori method for determining the most desirable product can produce a suffix, namely association rules that can be carried out properly in the form of a Website with the PHP programming language and the Laravell Framework and using the MySQL database. Testing is calculated by means of calculations using the Apriori formula itself with a specified amount of Support and Confidence determined, in this study the final result of the association rules is to produce 50% Support and 100% Confidence for the sale of Robusta Dampit and Arabica Wonosalam, 33.3% Support and 80% for Robusta Dampit and Hoseblend, 66.6% Support and 80% Confidence for Robusta Wonosalam and Arabica Wonosalam, 66.6% Support and 80% Confidence for Robusta Wonosalam and Hoseblend 70/30%, as well as 83.3% Support and 100% Confidence for Arabica Wonosalam and Hoseblend 70/30% with calculations using the a priori formula. Keywords:The Apriori Method, Coffee Beans, Roastery